Ascorbic acid electrochemical sensor based on poly-o-phenylenediamine micron material and application of ascorbic acid electrochemical sensor
The preparation of polyophenyldiamine micron material is done by chemical oxidation method, and the concentration of oxidant and NaCl is regulated, and the electrochemical sensor is modified, which solves the problem of insufficient sensitivity and selectivity of ascorbic acid detection, and achieves efficient and low-cost ultra-low concentration detection.
Patent Information
- Application Number
- CN202411248514.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing ascorbic acid detection technology has shortcomings in terms of sensitivity and selectivity. The traditional methods are complex and costly. It is difficult for the market to meet the requirements of high sensitivity and selectivity.
Materials with different morphology were prepared by chemical oxidation method, the types of oxidants and NaCl concentration were regulated, and the electrochemical sensors were modified to improve the detection sensitivity and selectivity of ascorbic acid.
The ultra-low concentration detection of ascorbic acid in ultrapure water environment is achieved, reaching the detection lower limit of 0.1nM, providing a new detection technology that is fast, efficient and cost-effective.
Smart Images

Figure CN119125254A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensing, and in particular relates to an ascorbic acid electrochemical sensor based on poly-o-phenylenediamine micron material and application thereof. Background Art
[0002] Ascorbic acid (vitamin C) is an essential water-soluble vitamin for the human body. It is widely present in a variety of foods and organisms and has important physiological functions such as anti-oxidation and promotion of collagen synthesis. Accurate determination of ascorbic acid is of great significance in clinical medicine, food industry and biochemical research. Traditional ascorbic acid detection methods such as high performance liquid chromatography (HPLC), although highly accurate, usually involve expensive equipment and complex operations, and are not suitable for rapid detection and field applications.
[0003] The rapid detection technologies currently on the market still face the problem of insufficient sensitivity and selectivity. For example, spectroscopy and titration methods are easily affected by sample color and turbidity, and although electrochemical sensors have the advantages of simple operation and low cost, existing material systems often cannot meet the requirements of high sensitivity and high selectivity at the same time.
[0004] Poly(o-phenylenediamine) is an important derivative of the conductive polymer polyaniline. Its molecular chain contains more amino (-NH2) and imino (=NH) active functional groups, which can form hydrogen bonds with the hydroxyl (-OH) and carboxyl (-COOH) groups in ascorbic acid molecules. The formation of these hydrogen bonds enhances the selective adsorption of poly(o-phenylenediamine) on ascorbic acid, allowing it to selectively recognize ascorbic acid molecules.
[0005] In addition, poly(o-phenylenediamine) is used to selectively identify ascorbic acid molecules through its unique porous structure and high surface area. These structural features provide a large number of electrochemically active sites for the oxidation reaction of ascorbic acid, enabling it to be effectively captured and identified. Poly(o-phenylenediamine) has good conductive properties and can achieve ultra-sensitive detection of ascorbic acid molecules. On the electrode surface, ascorbic acid is easily oxidized to produce a characteristic current peak. Electrodes modified with poly(o-phenylenediamine) can significantly amplify this current change, thereby improving the detection sensitivity. By controlling the preparation conditions, the obtained clustered poly(o-phenylenediamine) can increase its effective contact area with ascorbic acid molecules. This structure further enhances the electrochemical activity and detection sensitivity of the electrode, enabling it to detect ascorbic acid more accurately and sensitively.
[0006] Although poly(o-phenylenediamine) has been studied for use in electrochemical sensors, most studies focus on its homogeneous morphology, ignoring the potential to optimize performance by regulating its microstructure. Therefore, developing a new electrochemical sensor based on structure-controllable poly(o-phenylenediamine) micromaterials for efficient and accurate ascorbic acid detection is a technical problem that needs to be solved in this field. Summary of the invention
[0007] The purpose of the present invention is to provide an ascorbic acid electrochemical sensor based on poly-o-phenylenediamine micron material and application thereof.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention is to provide a method for preparing a poly(o-phenylenediamine) micron material, comprising the following steps:
[0010] The o-phenylenediamine solution with a concentration of 0.1 mol / L is prepared by dissolving o-phenylenediamine in water from which oxygen has been removed; the prepared o-phenylenediamine solution is mixed with a NaCl solution and a diluent, and after being shaken well, an oxidant solution is added, and the mixture is allowed to react to obtain a cluster-shaped, micron-belt-shaped or lath-shaped poly-o-phenylenediamine micron material;
[0011] When the prepared poly-o-phenylenediamine micron material is in cluster shape, the diluent is water, the oxidant solution is a 0.5 mol / L CuCl2 solution, the concentration of the NaCl solution is 3.09 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:1:1:0.5;
[0012] When the prepared poly-o-phenylenediamine micron material is in the shape of a micron ribbon, the diluent is water, the oxidant solution is a 0.5 mol / L CuCl2 solution, the concentration of the NaCl solution is 6.18 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:1:1:0.5;
[0013] When the prepared poly-o-phenylenediamine micron material is in the form of strips, the diluent is a 0.12 mol / L HCl solution, the oxidant solution is a 30 wt.% H2O2 solution, the concentration of the NaCl solution is 6.18 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:0.5:1:0.5.
[0014] Preferably, the water deoxygenated is prepared by passing N2 into water.
[0015] Preferably, the static reaction is specifically to stand for 15 minutes and continue the reaction for 12 hours.
[0016] Preferably, the static reaction further comprises a separation step, which specifically comprises centrifuging the reaction system after the static reaction, removing the supernatant, repeatedly washing with water, centrifuging to remove water, and finally drying to obtain the poly-o-phenylenediamine micron material.
[0017] The second technical solution of the present invention provides a poly(o-phenylenediamine) micron material prepared according to the preparation method of the poly(o-phenylenediamine) micron material.
[0018] The third technical solution of the present invention is to provide an ascorbic acid electrochemical sensor based on the above-mentioned poly-o-phenylenediamine micron material, wherein the surface of the working electrode of the ascorbic acid electrochemical sensor is coated with the poly-o-phenylenediamine micron material.
[0019] A fourth technical solution of the present invention is to provide an application of the above-mentioned ascorbic acid electrochemical sensor in detecting ascorbic acid.
[0020] The beneficial technical effects of the present invention are as follows:
[0021] The present invention adopts a chemical oxidation method, and synthesizes poly-o-phenylenediamine micron materials with different morphologies by screening the types of oxidants and adjusting parameters such as NaCl concentration, which can significantly enhance the interaction between the poly-o-phenylenediamine micron materials and ascorbic acid. The prepared poly-o-phenylenediamine micron materials are used to modify electrochemical sensors, which can improve the detection sensitivity and selectivity of the electrochemical sensors to ascorbic acid, and provide a new rapid, efficient and low-cost ascorbic acid detection technology for clinics and laboratories.
[0022] The results of electrochemical tests show that the prepared clustered poly(o-phenylenediamine)-modified electrode can detect ultra-low concentrations of ascorbic acid molecules, and can reach a detection limit of 0.1 nM in an ultrapure water environment, indicating that the ascorbic acid sensor has high sensitivity and that the use of low-cost poly(o-phenylenediamine) materials can simply and sensitively detect ascorbic acid in the nM range. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The SEM images and infrared spectra of the poly-o-phenylenediamine materials prepared in Examples 1-3, wherein a is the SEM image of the clustered poly-o-phenylenediamine material prepared in Example 1, b is the SEM image of the micron-belt poly-o-phenylenediamine material prepared in Example 2, c is the SEM image of the strip-shaped poly-o-phenylenediamine material prepared in Example 3, and d is the infrared spectra of the poly-o-phenylenediamine materials prepared in Examples 1-3.
[0024] Figure 2 This is a structural diagram of the ascorbic acid electrochemical sensor prepared using clustered poly-o-phenylenediamine as the electrode material in Example 4.
[0025] Figure 3These are the cyclic voltammetry (CV) test curves of the three ascorbic acid electrochemical sensors prepared in Example 4 for 1 mM ascorbic acid, wherein a is an electrochemical sensor coated with cluster-shaped poly-o-phenylenediamine, b is an electrochemical sensor coated with micron-belt poly-o-phenylenediamine, and c is an electrochemical sensor coated with strip-shaped poly-o-phenylenediamine.
[0026] Figure 4 These are the chronoamperometric response results of the three ascorbic acid electrochemical sensors prepared in Example 4 to ascorbic acid, wherein a is an electrochemical sensor coated with clustered poly-o-phenylenediamine, b is an electrochemical sensor coated with micron-belt poly-o-phenylenediamine, and c is an electrochemical sensor coated with strip-shaped poly-o-phenylenediamine.
[0027] Figure 5 The chronoamperometric response results of the electrochemical sensor coated with clustered poly-o-phenylenediamine prepared in Example 4 to ascorbic acid at different concentrations below 10 nM.
[0028] Figure 6 This is the chronoamperometric response result of the electrochemical sensor coated with clustered poly-o-phenylenediamine prepared in Example 4 to 0.1 nM ascorbic acid. DETAILED DESCRIPTION
[0029] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0030] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] Example 1
[0034] Preparation of clustered poly(o-phenylenediamine) materials:
[0035] (1) Take a 50 mL brown glass bottle, add 10 mL of deionized water at room temperature into the brown glass bottle, and continuously pass high-purity N2 (99.999%) gas into the bottle for 30 min to remove all oxygen in the water;
[0036] (2) Weigh 0.108 g of o-phenylenediamine monomer at room temperature, quickly add it to a brown glass bottle and mix it with water, seal it, and use a magnetic stirrer to stir at a constant temperature until it is completely dissolved to obtain a colorless transparent liquid. The resulting solution is 0.1 mol / L o-phenylenediamine;
[0037] (3) Seal the bottle with tin foil and store the resulting solution at 3°C. Make sure the solution is used up within 20 minutes before use.
[0038] (4) Take 0.5 mL of 0.1 mol / L o-phenylenediamine solution, add 1 mL of 3.09 mol / L NaCl solution and 1 mL of deionized water, shake well and quickly add 0.5 mL of 0.5 mol / L CuCl2 solution. Observe that the color of the solution quickly changes from blue to dark green.
[0039] (5) After standing for 15 minutes, a large amount of dark green precipitate was observed in the solution. The reaction was continued for 12 hours to complete the reaction. The centrifuge speed was set to 5000 r / min and centrifuged for 10 minutes to remove the supernatant and retain the bottom precipitate. The precipitate was washed with deionized water three times and finally dried in a vacuum drying oven at 50°C to obtain clustered poly-o-phenylenediamine.
[0040] Example 2
[0041] Preparation of micron-ribbon poly(o-phenylenediamine) material:
[0042] The difference from Example 1 is that in step (4), 1 mL of 3.09 mol / L NaCl solution is changed to 1 mL of 6.18 mol / L NaCl saturated solution, and the color of the formed precipitate is brown.
[0043] Example 3
[0044] Preparation of lath-like poly(o-phenylenediamine) materials:
[0045] The difference from Example 1 is that in step (4), 1 mL of 3.09 mol / L NaCl solution, 1 mL of deionized water, and 0.5 mL of 0.5 mol / L CuCl2 solution are changed to 0.5 mL of 6.18 mol / L NaCl saturated solution, 1 mL of 0.12 mol / L HCl solution, and 0.5 mL of 30 wt.% H2O2 solution, and the color of the precipitate formed is brown.
[0046] The SEM images and infrared spectra of the poly-o-phenylenediamine materials prepared in Examples 1-3 are shown in Figure 1 , wherein a is the SEM image of the clustered poly-o-phenylenediamine material prepared in Example 1, b is the SEM image of the micron-belt poly-o-phenylenediamine material prepared in Example 2, c is the SEM image of the lath-shaped poly-o-phenylenediamine material prepared in Example 3, and d is the infrared spectrum of the poly-o-phenylenediamine materials prepared in Examples 1-3.
[0047] In Example 1, CuCl2 was used as an oxidant, and a certain amount of o-phenylenediamine monomer and NaCl solution were mixed. 2+ After being reduced, the poly(o-phenylenediamine) oligomers self-assemble to form a clustered poly(o-phenylenediamine) structure.
[0048] Compared with Example 1, Example 2 increases the NaCl concentration to increase the electrostatic repulsion of the poly(o-phenylenediamine) oligomers, hindering the self-assembly process and forming a micron-belt poly(o-phenylenediamine) structure.
[0049] In Example 3, H2O2 is used as an oxidant to form a strip-like poly(o-phenylenediamine) structure.
[0050] like Figure 1 As shown in the middle d, 1237cm -1 The infrared peak at 1367cm is caused by the stretching vibration of the CN bond of the benzene ring. -1 The infrared peak at 1673cm is caused by the stretching vibration of the CN bond of the quinone ring. -1 The peak at 3176 cm is the vibration peak of C=N in the phenazine ring. -1 and 3356cm -1 The infrared peaks at are caused by the stretching vibration of NH2 in NH and the stretching vibration of NH in NH. During the polymerization of o-phenylenediamine molecules, -NH2 on the o-phenylenediamine molecules is oxidized to form two active sites, and then through mutual collision and contact between molecules, a phenazine-like structure is gradually formed. As the reaction time increases, the molecular weight gradually increases, and a poly-o-phenylenediamine structure with a high degree of polymerization is generated. The appearance of the above characteristic peaks indicates that the formed polymer contains a phenazine ring structure, confirming the formation of poly-o-phenylenediamine.
[0051] Example 4
[0052] Preparation of ascorbic acid electrochemical sensor based on poly(o-phenylenediamine) micron material of Examples 1-3:
[0053] (1) 8 mg of the cluster-shaped, micron-shaped, and lath-shaped poly-o-phenylenediamine powders prepared in Example 1, Example 2, and Example 3 were respectively dissolved in 200 μL of water, and ultrasonically treated at 150 W for 30 min to obtain inks A, B, and C;
[0054] (2) using a screen printer to print a conductive silver paste on a polyimide substrate as an electrode lead, and drying at room temperature for 24 hours to obtain an electrode lead layer;
[0055] (3) printing a working electrode and a counter electrode on a polyimide substrate using carbon paste, and drying at room temperature for 24 h to obtain a working electrode layer and a counter electrode layer;
[0056] (4) printing a reference electrode on a polyimide substrate using a silver / silver chloride paste and drying at room temperature for 24 h to obtain a reference electrode layer;
[0057] (5) Inks A, B, and C are uniformly coated on the surface of the working electrode, respectively, and dried at room temperature to obtain an ascorbic acid electrochemical sensor. The structure of the ascorbic acid electrochemical sensor prepared using clustered poly-o-phenylenediamine as the electrode material is shown in Figure 2 .
[0058] Example 5
[0059] Application of the three ascorbic acid electrochemical sensors prepared in Example 4 in detecting ascorbic acid:
[0060] (1) Prepare a test solution containing supporting electrolytes (PBS buffer solution) and add a known concentration of ascorbic acid;
[0061] (2) immersing the modified electrode in a test solution containing ascorbic acid, performing cyclic voltammetry scanning using an electrochemical workstation, setting the scanning potential range to -0.6 V to 0.6 V, the scanning rate to 50 mV / s, recording the current-voltage curve, and observing the oxidation peak and reduction peak of ascorbic acid at a specific potential;
[0062] (3) The current response signal of ascorbic acid of different concentrations was measured using the chronoamperometry method. A fixed potential (ascorbic acid oxidation peak potential, 0.4 V) was applied and the current versus time curve was measured at the fixed potential. The concentration of ascorbic acid in the solution was calculated based on the change in the current peak value, and the performance of the sensor was optimized by adjusting the electrode parameters and test conditions.
[0063] The cyclic voltammetry (CV) test curves of the three ascorbic acid electrochemical sensors prepared in Example 4 for 1 mM ascorbic acid are shown in Figure 3 , wherein a is an electrochemical sensor coated with cluster-shaped poly-o-phenylenediamine, b is an electrochemical sensor coated with micron-belt-shaped poly-o-phenylenediamine, and c is an electrochemical sensor coated with strip-shaped poly-o-phenylenediamine. Figure 3It shows that in the presence of ascorbic acid molecules, the current response of three types of poly-o-phenylenediamine gradually increases from 0.4V, proving that poly-o-phenylenediamine has an electrochemical response to ascorbic acid molecules. According to the CV test results, 0.6V was selected as the working voltage of the sensing electrode to detect ascorbic acid of different concentrations.
[0064] Figure 4 The chronoamperometric response results of the three ascorbic acid electrochemical sensors prepared in Example 4 to ascorbic acid, wherein a is an electrochemical sensor coated with clustered poly-o-phenylenediamine, b is an electrochemical sensor coated with micron-belt poly-o-phenylenediamine, and c is an electrochemical sensor coated with strip-shaped poly-o-phenylenediamine. By comparing the current response results of materials with different morphologies to 10 nM ascorbic acid solution, it is concluded that clustered poly-o-phenylenediamine has a relatively high current response value to ascorbic acid molecules.
[0065] Figure 5 The chronoamperometric response results of the electrochemical sensor coated with clustered poly-o-phenylenediamine to ascorbic acid at different concentrations below 10 nM. When detecting low-concentration ascorbic acid, the inventors found that the complex ions in the electrolyte solution would affect the selective adsorption of ascorbic acid molecules on the electrode surface, making it difficult to achieve ultra-low concentration detection. For ultra-low concentration ascorbic acid detection, the present invention directly dilutes the ascorbic acid solution in deionized water, and allocates 0.5 nM, 1 nM and 10 nM solutions for chronoamperometric detection. Figure 5 It can be seen that with clustered poly-o-phenylenediamine as the electrode material, different concentrations of ascorbic acid solutions below 10 nM were detected, and an obvious current response signal appeared, and as the ascorbic acid concentration increased, the current response signal gradually increased. By comparing different curves, it can be seen that the prepared clustered poly-o-phenylenediamine electrode can achieve 0.5 nM ascorbic acid detection in a pure water environment.
[0066] Figure 6 The chronoamperometric response results of the electrochemical sensor coated with clustered poly(o-phenylenediamine) to 0.1 nM ascorbic acid. The electrochemical test results show that the electrode modified with clustered poly(o-phenylenediamine) can detect ultra-low concentrations of ascorbic acid molecules, and can reach a detection limit of 0.1 nM in an ultrapure water environment. In addition, the ultra-low concentration detection limit shows that the ascorbic acid sensor has high sensitivity, and the use of low-cost poly(o-phenylenediamine) materials can simply and sensitively detect ascorbic acid in the nM range.
[0067] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a poly(o-phenylenediamine) micron material, characterized in that: The following steps are involved: The o-phenylenediamine solution with a concentration of 0.1 mol / L is prepared by dissolving o-phenylenediamine in water from which oxygen has been removed; the prepared o-phenylenediamine solution is mixed with a NaCl solution and a diluent, and after being shaken well, an oxidant solution is added, and the mixture is allowed to react to obtain a cluster-shaped, micron-belt-shaped or lath-shaped poly-o-phenylenediamine micron material; When the prepared poly-o-phenylenediamine micron material is in cluster shape, the diluent is water, the oxidant solution is a 0.5 mol / L CuCl2 solution, the concentration of the NaCl solution is 3.09 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:1:1:0.5; When the prepared poly-o-phenylenediamine micron material is in the shape of a micron ribbon, the diluent is water, the oxidant solution is a 0.5 mol / L CuCl2 solution, the concentration of the NaCl solution is 6.18 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:1:1:0.5; When the prepared poly-o-phenylenediamine micron material is in the form of strips, the diluent is a 0.12 mol / L HCl solution, the oxidant solution is a 30 wt.% H2O2 solution, the concentration of the NaCl solution is 6.18 mol / L, and the volume ratio of the o-phenylenediamine solution, the NaCl solution, the diluent and the oxidant solution is 0.5:0.5:1:0.
5.
2. The method for preparing the poly-o-phenylenediamine micron material according to claim 1, characterized in that: The water deoxygenated is prepared by passing N2 into water.
3. The method for preparing the poly-o-phenylenediamine micron material according to claim 1, characterized in that: The static reaction is specifically to stand for 15 minutes and continue the reaction for 12 hours.
4. The method for preparing the poly-o-phenylenediamine micron material according to claim 1, characterized in that: The method further comprises a separation step after the standing reaction, wherein the separation step specifically comprises centrifuging the reaction system after the standing reaction, removing the supernatant, repeatedly washing with water, centrifuging to remove water, and finally drying to obtain the poly-o-phenylenediamine micron material.
5. A poly(o-phenylenediamine) micron material obtained according to the method for preparing a poly(o-phenylenediamine) micron material according to any one of claims 1 to 4.
6. An ascorbic acid electrochemical sensor based on the poly(o-phenylenediamine) micron material according to claim 5, characterized in that: The surface of the working electrode of the ascorbic acid electrochemical sensor is coated with the poly-o-phenylenediamine micron material.
7. Use of the ascorbic acid electrochemical sensor according to claim 6 in detecting ascorbic acid.
Citation Information
Patent Citations
Method for preparing poly(o-phenylenediamine) nanomicelle by utilizing aqueous phase method
CN103694471A
Method for preparing poly(o-phenylenediamine) nanoribbon by utilizing aqueous phase method
CN103694473A
Method for preparing poly(o-phenylenediamine) fluorescent nano-belt by virtue of water-phase method
CN103788369A
Method for preparing poly-o-phenylenediamine microspheres by using green oxidant
CN105218809A
Glassy carbon electrode modified with a graphene oxide / poly(o-phenylenediamine) composite for chemical detection and the preparation method thereof
KR101680482B1
